THE INFLUENCE OF STUDENT CHARACTER AND LEARNING STYLE AGAINST LEARNING OUTCOMES OF ISLAMIC RELIGIOUS EDUCATION DARUSSALAM ICT VOCATIONAL SCHOOL STUDENTS IN MEDAN - Noor, Muhammad Zein; Soiman, Soiman; Sabri, Rijal (Universitas Dharmawangsa, 2023)
This study aims to determine: (1) the character of students in SMK TIK Darussalam Medan in learning Islamic Religious Education; (2) student learning styles at SMK TIK Darussalam Medan in Islamic Religious Education learning; (3) the influence of students' character and learning styles on learning outcomes in Islamic Religious Education learning for students of SMK TIK Darussalam Medan. This thesis is prepared based on field data using quantitative research using associative methods. Associative research is research that aims to find the relationship between two or more variables. The nature of this research is causal correlation. This study uses a survey research strategy that uses structured questionnaires or interviews for data collection, focusing on generalizations. The results showed that: (1) there was a positive and significant influence between the character of students on PAI learning outcomes for class XII students of SMK TIK Darussalam Medan with Fcount = 25.81, Ftable = 3.96, so that Fcount>Ftable (25.81). > 3.96,); (2) there is a positive and significant influence between student learning styles on PAI learning outcomes for class XII students of SMK TIK Darussalam Medan with a price of Fcount = 24.32 Ftable value = 3.96 so that the value of Fcount>Ftable (24.32> 3.96 ,); (3) there is a positive and significant effect between student character and learning style on PAI learning outcomes for class XII students of SMK TIK Darussalam Medan with Freg = 19.18 and obtained F5% = 3.32 so Freg > F5% (19.18 > 3.32).